Effects of nanoparticle shape and size on the thermohydraulic performance of plate evaporator using hybrid nanofluids - Bhattad A.; Sarkar J. (My University, 2025)
Brines (ethylene glycol, calcium chloride, propylene glycol and potassium acetate)-based hybrid (combinations of alumina, copper oxide, silica and titania with copper nanoparticles) nanofluids have been used as a secondary refrigerant to improve the heat transfer characteristics of the plate evaporator for milk chilling. Effect of nanoparticle combination, shape and size on heat transfer area, pump work, the ratio of heat transfer coefficient to pressure drop, coefficient of performance, performance index, thermal performance factor and exergetic efficiency has been examined theoretically. Copper oxide–copper hybrid nanofluid gives superior performance, while silica–copper hybrid nanofluid performs well in terms of exergetic efficiency. The maximum decrease in effective heat transfer area (5.9%) is found for propylene glycol brine-based copper oxide hybrid nanofluid. Percentage change in heat transfer area and performance index reduces with an increase in the particle size and is maximum for alumina–copper hybrid nanofluid. However, thermal performance factor increases with particle size. Brick-shaped particles show maximum changes in heat transfer area and performance index, while platelet-shaped particles show worse performance. The study reveals that the nanoparticle shape has a strong influence on the plate heat exchanger performance due to a significant deviation in surface area-to-volume ratio. © 2019, Akadémiai Kiadó, Budapest, Hungary.